DESIGN AND CALCULATION OF AERODROMECOAING WITH HEATED SURFACE LAYERS - Piskunov, Vadim G.; Volodko, Olga V.; Demchyk, Oleg M. (Proceedings of National Aviation University (archive), 2009)
The developed constructions with heated by surface layers for aerodromes and auto roads when developed composition of electroconductive concrete reinforced with chemical electrical conductive fibres being used was researched. The experimentally obtained characteristics of ended conductive concrete reinforced with fibers were presented. Calculation by developed heated construction of shell was made.